Protocol for the comparison of triflusal and clopidogrel in secondary prevention of stroke based on cytochrome P450 2C19 genotyping (MASETRO study): A multicenter, randomized, open-label, parallel-group trial. Issue 4 (June 2016) - Han, Sang Won; Kim, Yong-Jae; Ahn, Seong Hwan; Seo, Woo-Keun; Yu, Sungwook; Oh, Seung-Hun; Kim, Youn Nam; Lee, Kyung-Yul
Rationale and aim: The antiplatelet effect of clopidogrel is reportedly influenced by cytochrome P450 2C19 (CYP2C19) polymorphisms. However, there is no data concerning the relationship between stroke recurrence and CYP2C19 polymorphisms in patients treated with clopidogrel for secondary prevention of ischemic stroke. Triflusal may be an alternative therapy for clopidogrel in patients with poor genotype. The Comparison of Triflusal and Clopidogrel Effects in Secondary Prevention of Stroke Based on Cytochrome P450 2C19 Genotyping (MAESTRO) study will investigate the effect of antiplatelet agents based on CYP2C19 polymorphisms in secondary prevention of ischemic stroke. Sample size and design: Assuming that 55% of patients belong to the poor genotype group, the required sample size is 1080 patients with at least 24 months of follow-up. This study is designed as a prospective, multicenter, randomized, parallel-group, open-label, and blind genotype trial. Patients who experience their first non-cardiogenic ischemic stroke within 30 days prior to screening are eligible. Patients received 300 mg triflusal twice a day or 75 mg clopidogrel once daily during the trial. The study is registered with ClinicalTrials.gov (NCT01174693). Study outcome: The primary outcome is recurrent ischemic stroke or hemorrhagic stroke. Secondary outcomes consist of composite major vascular events including stroke, myocardial infarction, coronary revascularization, or vascular death. Discussion: Personalized medicine may be essential for patients according to individual drug metabolism abilities. MAESTRO is the first prospective study designed to evaluate the effect of CYP2C19 polymorphism in secondary stroke prevention and will resolve several questions regarding preventive antiplatelet agents for recurrent stroke.